Fast and Accurate Motion Control Based on Good Gain Method - GAO Qingji; LI Zheng (Institute of Advanced Engineering and Science, 2013)
There are some drawbacks exist in multi-method intelligence control algorithms which are popular researched in motion control. Many of the most significant ones are high algorithm complexity, long time-consuming and not easily applied in industrial production. According to the disadvantages mentioned above, and also take the conflicts between control accuracy and response speed into consideration, a “Good Gain” PID tuning method is studied on motion control. Firstly this PID tuning method is described and the processes of finding proper PID gains by analyzing the outputs of PID controller are designed. Secondly the method is simulated on a DC motor model and finally acquires a proper balance between response speed and control accuracy. Finally the method is tested on real DC motor and control devices. After software simulation and real experiments, the effectiveness of this PID tuning method is proved. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2191